The Dome of the Rock and its Umayyad mosaic inscriptions - Milwright, Marcus (Edinburgh studies in Islamic art., 2016)
The Dome of the Rock is a shrine located on the Temple Mount in the Old City of Jerusalem. When was it built? What meanings was it meant to convey to viewers at the time of its construction? These are questions that have preoccupied historians of Islamic art and architecture, and numerous interpretations of the Dome of the Rock have been proposed. Marcus Milwright returns to one of the most important pieces of evidence: the mosaic inscriptions running around the two faces of the octagonal arcade. His detailed examination of the physical characteristics, morphology and content of these inscriptions provides new evidence about the chronology the building and the iconography of the Dome of the Rock.